The Dead Sea Scrolls Concordance, Volume 1.2 : The Non-Biblical Texts from Qumran. - Abegg, Martin G. (Biblical Studies, Ancient Near East and Early Christianity - Book Archive 2000-2006., 2003)
For decades a concordance of all the Dead Sea Scrolls has been a major desideratum for scholarship. The Dead Sea Scrolls Concordance covers all the Qumran material as published in the Discoveries in the Judaean Desert series, as well as the major texts from caves 1 and 11, which appeared elsewhere. This keyword-in-context concordance, prepared by Martin G. Abegg in collaboration with other scholars, contains a new and consistent linguistic analysis of all the words found in the Dead Sea Scrolls. The total number of entries is around 134,000. Every entry includes the keyword with its context, exactly as published in the editions referred to above, with notes on some readings. All keywords have an English translation, and they are listed in alphabetical order rather than by verbal root, which makes the concordance easier to consult for the non-specialist. This concordance to the non-biblical texts from Qumran is the first of a projected series of three. Future volumes will consist of concordances to the biblical texts from Qumran and to the texts from other sites in the Judean Desert. The print edition is available as a set of two volumes (9789004125216).